Letter: synergistic role of gut flora with aspirin to prevent colorectal cancers—authors' reply. Issue 11 (18th November 2020) - Prizment, Anna E.; Onyeaghala, Guillaume C.; Church, Timothy R.
Abstract : LINKED CONTENT This article is linked to Prizment et al and Li et al papers. To view these articles, visit https://doi.org/10.1111/apt.16013 and https://doi.org/10.1111/apt.16093